Strategi Guru PPKn dalam Pelaksanaan Penguatan Karakter Disiplin pada Peserta Didik Kelas X MAN 2 Lamongan - Lucyana Varda; Oksiana Jatiningsih (Kajian Moral dan Kewarganegaraan, 2023)
This study aims to describe the strategies used by PPKn teachers in strengthening the character of discipline and the obstacles faced along with the solutions offered to strengthen the character of discipline in class X students of MAN 2 Lamongan. This study uses a qualitative approach with a descriptive method. This study uses the theory of Character Education proposed by Thomas Lickona. The informants of this study were two people selected using purposive sampling technique, namely two PPKn teachers. Data collection techniques using observation, interviews, and documentation, then analyzed with the stages of data collection, data reduction, data presentation, and drawing conclusions. Based on the results of the study, it can be concluded that there are several strategies carried out by Civics teachers in strengthening the discipline character of class X students in planning, namely the preparation of the Learning Implementation Plan (RPP). In the implementation of strengthening the character of discipline according to the Learning Implementation Plan (RPP), which was previously designed. These include preliminary activities, core activities, and closing activities. In addition, teachers make learning contracts in learning, habituation of teachers by giving good examples, students can behave politely, be disciplined and dress neatly, and give rewards to students in the form of grades or points and words of praise. Constraints experienced by Civics teachers in strengthening the character of discipline are the lack of self-awareness of students and the influence of the unfavorable community environment. The solution to overcome the obstacles to strengthening the character of discipline is to provide advice and provide punishment in the form of memorizing short chapters of chapter 30 and Pancasila.